Inside Back Cover: Transient Interactions of a Cytosolic Protein with Macromolecular and Vesicular Cosolutes: Unspecific and Specific Effects (ChemBioChem 18/2015). Issue 18 (December 2015) - Ceccon, Alberto; Busato, Mirko; Pérez Santero, Silvia; D'Onofrio, Mariapina; Musiani, Francesco; Giorgetti, Alejandro; Assfalg, Michael
Abstract : The inside back cover picture shows the types of transient interaction experienced by a test cytosolic protein, with macromolecules and vesicles mimicking intracellular components. Ileal bile acid binding protein (IBABP, shown in red) is not attracted by a small neutral macromolecule (green and white, top left); however, it shows unspecific interactions with the acidic protein albumin (brown and white, bottom right) and forms stereospecific complexes of ultraweak affinity with lysozyme (blue and white, bottom left). The adsorption of IBABP to lipid vesicles (top right) is weak and mediated by a preferential surface region. In most cases, localized dynamic effects are observed (yellow circles)."